PENENTUAN SIFAT TERMAL CABAI PUYANG (Piper retrofractum Vahl.) KERING PADA TIGA TAHAP KEMATANGAN - La Choviya Hawa; Addieny Sugesti; Yusuf Wibisono; Siti Asmaniyah Mardiyani (AGROINTEK, 2022)
Dried cabya (Piper retrofractum Vahl.) is commonly used in making various types of herbs, spices, and cosmetic raw materials that require heating processes so that they require information on the value of thermal conductivity (k), thermal diffusivity (α), and specific heat (Cp). The thermal properties of dried cabya are affected by different phytochemical compositions at each maturity stage of the fruit. This study aims to determine and analyze the thermal properties and phytochemical content of dried cabya in three stages of green, orange and red maturity. Measurement of thermal diffusivity in this study uses the principle of onedimensional unsteady-state conduction heat flow using a vertical thermal diffusivity test. The value of thermal conductivity is determined indirectly by a calculation method based on the value of thermal diffusivity, specific heat, and density of the material. The thermal conductivity values of green, orange, and red paste cabya are 0.241 ± 0.016, 0.298 ± 0.005, and 0.344 ± 0.025 W/m°C. Reducing sugar levels in dried green, orange, and red cabya are 2.32 ± 0.16, 4.07 ± 0.13, and 6.44 ± 0.13 %, piperine levels are 2.42 ± 0.01, 1.97 ± 0.06, and 1.54 ± 0.05 %, and antioxidant levels are 87.15, 75.26, and 63.38 mg/mL. Based on the results of the study, red dried cabya have higher values of α, Cp, and k compared to orange and green because they contain higher levels of water and reducing sugars. However, red dried cabya have piperin and antioxidant levels which are getting lower